PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2025 - Elvina Widya Sari; Apriya Santi; Siti Mardah (Publika Citra Media, 2026)
This study aims to determine the effect of: (1) liquidity on company profitability (2) leverage on company profitability (3) liquidity and leverage simultaneously on profitability in food and beverage companies listed on the Indonesia Stock Exchange for the 2022–2025 period. This study uses a quantitative approach with secondary data in the form of company annual financial reports. The population consists of 83 food and beverage companies listed on the IDX. Through purposive sampling, 40 sample companies were obtained, with a total of 121 observations after removing outliers. The independent variables were measured using the Current Ratio (CR) for liquidity and the Debt to Equity Ratio (DER) for leverage. The dependent variable was measured using Return on Assets (ROA) for profitability. Data analysis used multiple linear regression with SPSS version 27. The results show that: (1) Liquidity has a positive and significant effect on profitability (2) Leverage has a negative and significant effect on profitability (3) Liquidity and Leverage simultaneously have a significant effect on profitability.